2021
DOI: 10.2196/24135
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Health Risk Behavior Screening With Integrated Feedback Among Adolescents in Primary Care: Randomized Controlled Trial

Abstract: Background Health risk behaviors are the most common sources of morbidity among adolescents. Adolescent health guidelines (Guidelines for Preventive Services by the AMA and Bright Futures by the Maternal Child Health Bureau) recommend screening and counseling, but the implementation is inconsistent. Objective This study aims to test the efficacy of electronic risk behavior screening with integrated patient-facing feedback on the delivery of adolescent-r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, more digitalized fitness programs were chosen, which is in line with a study of Parker et al. ( 2021 ) who reported higher physical activity of those people who practice sport or physical activity with the help of a digitized form.…”
Section: Change Of Type Of Sport and Physical Activity During The Coronavirus Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, more digitalized fitness programs were chosen, which is in line with a study of Parker et al. ( 2021 ) who reported higher physical activity of those people who practice sport or physical activity with the help of a digitized form.…”
Section: Change Of Type Of Sport and Physical Activity During The Coronavirus Pandemicmentioning
confidence: 99%
“…However, it is known that participants who used digital platforms for physical activity had a higher moderate-to-vigorous intensity physical activity and muscle-strength training than nonusers (Parker et al., 2021 ). In Germany, leisure time sport and exercise decreased for 31% of Germans, while 27% retained and 6% even intensified their level.…”
mentioning
confidence: 99%
“…Moreover, mental and behavioral health outcomes, including depression and disorders related to the use of alcohol and other substances, have gained much attention in recent years [ 1 ]. Adolescent HRBs generally cause direct or indirect damage to the health, well-being, and quality of life of adolescents [ 2 ]. A cohort study identified two latent classes of HRBs: a risky-behavior class (men: 20.0% and women: 23.6%), including smoking and binge drinking, and a less-risky-behavior class [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that prescreening youth for a variety of health and behavioral concerns increases recognition of these issues by HCPs, 17,18 though to our knowledge this has not been examined for firearms. In this article, we examine the extent to which utilizing the electronic medical record (EMR) to convey information from patient screening about firearm access to the HCP can influence the delivery of safe firearm storage messages by the HCP.…”
Section: Role Of Hcpsmentioning
confidence: 93%
“…15 Importantly, pediatric trainees do not feel they are being taught to address gun safety, as 63% stated they never provide firearm-related counseling in any type of visit and do so only 15% of the time during well child visits. 16 Evidence suggests that prescreening youth for a variety of health and behavioral concerns increases recognition of these issues by HCPs, 17,18 though to our knowledge this has not been examined for firearms. In this article, we examine the extent to which utilizing the electronic medical record (EMR) to convey information from patient screening about firearm access to the HCP can influence the delivery of safe firearm storage messages by the HCP.…”
Section: Role Of Hcpsmentioning
confidence: 99%